Factors Affecting Consumers' Green Purchasing Behavior: An Integrated Conceptual Framework - Hans Ruediger Kaufmann; Mohammad Fateh Ali Khan Panni; Yianna Orphanidou (Amfiteatru Economic Journal, 2012)
In this modern era of societal marketing business ethics and social responsibility are becoming the guiding themes for marketing strategies and practices. Within the field of ethics and social responsibility environmental and green marketing topics are the central topics, which are closely related to biodiversity and sustainability. This paper suggests a different approach to assessing the variables of consumers' green purchasing behavior. Based on thoroughly researched secondary data, this conceptual paper suggests a framework integrating the so far incoherent frameworks as proposed by previous authors. Emanating from this eclectic and chronological literature review, the paper will also propose further missing links that need to be included in the proposed integrated framework. Based on this holistic framework, in a future study, the authors will explain a sustainability index of green consumer behavior, which will be tested empirically in the study. In fact, from the proposed integrated framework, in total eight vital factors/aspects of green/environmental issues are likely to have an impact on consumer green purchasing behavior. Demographic variables will play an intervening or mediating role in the framework.
Keywords: Q56; 330; pro-environmental consumer behaviour; sustainability; green consumer behavior; green purchasing